A method for preparing a core-shell structured Zn-OC single-atom electrocatalyst for synthesizing H2O2

Through the design of the Zn-O-C single atomic catalyst of the nuclear shell structure, the problem of complex H2O2 preparation process in the existing technology, high pollution, and high catalyst costs of precious metal catalysts have been solved, and efficient and green H2O2 synthesis is achieved, which is suitable for sewage treatment and other fields.

CN115433954BActive Publication Date: 2025-01-24HENAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210984827.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-17
Publication Date
2025-01-24
Estimated Expiration
2042-08-17

AI Technical Summary

Technical Problem

The existing industrial methods used to prepare H2O2 have problems such as high investment costs, complex processes, limited reserves of environmentally friendly and precious metal catalysts, and are difficult to meet the needs of green, environmentally friendly and sustainable development.

Method used

The Zn-O-C single atomic catalyst with a nuclear shell structure is introduced by the ZIF-8 with a rich oxygen-containing energy group as the front-drive body, and the S source is introduced during the high-temperature sintering process to synthesize the electrical catalyst that can efficiently prepare H2O2.

Benefits of technology

It achieves the synthesis of H2O2 in the electrochemical oxygen reduction reaction with high selectivity (90%). It is green, environmentally friendly, low-cost and efficient, and is suitable for sewage treatment and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115433954B_ABST
    Figure CN115433954B_ABST
Patent Text Reader

Abstract

The invention discloses a method for synthesizing H 2 O 2 The preparation method of the core-shell structure Zn-O-C electrocatalyst is based on the hollow structure ZIF-8 with rich oxygen-containing functional groups as the precursor. The S source is introduced during the high-temperature sintering process to prepare the electrocatalyst for the highly selective synthesis of H 2 O 2 The Zn-O-C single-atom electrocatalyst catalyzes the synthesis of H 2 O 2 The selectivity is as high as 90%. The preparation process of the invention is simple, and the raw materials of the electrocatalyst are widely available and the cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of synthesis of metal-supported electrocatalysts, and in particular relates to a method for preparing a core-shell structured Zn-OC single-atom electrocatalyst for synthesizing H2O2. Background Art

[0002] Hydrogen peroxide (H2O2) is a green, renewable, and environmentally friendly oxidant. It is widely used in medical disinfection, sewage treatment, pulp bleaching, fine chemicals, and other fields, and is listed as one of the world's 100 most important chemicals. Although H2O2 plays an increasingly important role in the development of green chemistry, the existing industrial anthraquinone method is not "green" enough. The preparation method has significant disadvantages such as high investment cost, complex process, environmental pollution, and inconvenient storage / transportation / use. Therefore, a new method for preparing H2O2 through the electrochemical oxygen reduction pathway has attracted attention as a potential alternative. The electrochemical oxygen reduction method has the advantages of simple reaction conditions, clean production process, and low time consumption. It is a safe, energy-saving, green and sustainable way to produce H2O2. At present, the catalysts used in the electrochemical oxygen reduction process to prepare H2O2 are mainly precious metal materials (Pd, Au, Ag, Pt-Hg, etc.). Due to their limited reserves and high prices, it is difficult to meet the needs of modern chemical industry for green, environmental protection and sustainable development. Single-atom electrocatalysts are favored by researchers because of their high atomic utilization, fully exposed active sites and 100% atomic utilization. They are expected to be used as alternative materials to precious metal catalysts in electrochemical oxygen reduction reactions. However, the synthesis of high-performance single-atom electrocatalysts is still a key bottleneck restricting the electrocatalytic synthesis of H2O2. Therefore, designing highly selective single-atom electrocatalysts is a top priority for achieving green production of H2O2. Summary of the invention

[0003] The technical problem solved by the present invention is to provide a method for preparing a core-shell structured Zn-OC single-atom electrocatalyst for synthesizing H2O2. The method uses ZIF-8 with a hollow structure and rich oxygen-containing functional groups as a precursor, introduces an S source during a high-temperature sintering process, and synthesizes a core-shell structured Zn-OC single-atom electrocatalyst capable of preparing H2O2.

[0004] The present invention adopts the following technical solution to solve the above technical problems: a method for preparing a core-shell structure Zn-OC single-atom electrocatalyst for synthesizing H2O2, characterized in that the specific steps are:

[0005] Step S1: mixing a methanol solution of 2-methylimidazole and a methanol solution of zinc salt, and allowing to stand, and then performing solid-liquid separation and drying to obtain polyhedral ZIF-8;

[0006] Step S2: The polyhedral ZIF-8 obtained in step S1 is stirred in a tannic acid solution, and then solid-liquid separation and drying are performed to obtain ZIF-8 with a hollow structure;

[0007] Step S3: placing the hollow structure ZIF-8 obtained in step S2 in a tube furnace, placing sublimated sulfur in front of the ZIF-8, heating to 600°C at a heating rate of 1-10°C / min under an inert gas atmosphere, and keeping the temperature constant for 2-4h, and then naturally cooling to room temperature;

[0008] Step S4: soaking the material obtained in step S3 with an acid solution, then filtering, washing with water until neutral, and drying to obtain a core-shell structured Zn-OC single-atom electrocatalyst for synthesizing H2O2, wherein the metal Zn in the core-shell structured Zn-OC single-atom electrocatalyst is supported on the nitrogen / sulfur co-doped carbon material in the form of a single atom, and the loading amount of the metal Zn is 2wt%~8wt%.

[0009] It is further defined that the molar ratio of 2-methylimidazole to zinc salt in step S1 is 1-8:1.

[0010] It is further defined that the concentration of tannic acid in step S2 is 3-8 g / L, and the stirring treatment time is 10-20 min.

[0011] It is further defined that the mass ratio of the hollow structure ZIF-8 and the sublimated sulfur in step S3 is 1:4-8.

[0012] It is further defined that the inert gas in step S3 is one or more of nitrogen, argon or helium.

[0013] It is further defined that the acid solution in step S4 is one or more of hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid or acetic acid, the concentration of the acid solution is 0.5~4M, the acid solution treatment temperature is 25~100°C, and the acid solution treatment time is 2~24h.

[0014] The method for preparing the Zn-OC electrocatalyst for synthesizing H2O2 of the present invention is characterized by the following specific steps:

[0015] Step S1: Pour 120 mL of methanol solution containing 2.38 g of zinc nitrate into 120 mL of methanol solution containing 2.13 g of 2-methylimidazole, let stand for 12 h, perform solid-liquid separation and drying to obtain polyhedral ZIF-8;

[0016] Step S2: 0.4 g of the polyhedral ZIF-8 obtained in step S1 is dispersed in 200 mL of a 5 g / L tannic acid solution and stirred for 10 min, followed by solid-liquid separation and drying to obtain ZIF-8 with a hollow structure;

[0017] Step S3: 0.2 g of the hollow structure ZIF-8 obtained in step S2 is placed in a tube furnace, and 0.04 g of sublimated sulfur is placed in front of the ZIF-8, and the temperature is increased to 600° C. at a heating rate of 3° C. / min under a nitrogen atmosphere for 3 h, and then naturally cooled to room temperature;

[0018] Step S4: Soak the material obtained in step S3 in 2M hydrochloric acid at room temperature for 24 hours, then filter it, wash it with water until it is neutral, and then dry it at 80°C to obtain a core-shell structured Zn-OC single-atom electrocatalyst for synthesizing H2O2.

[0019] The specific process of catalytic synthesis of H2O2 by the core-shell structure Zn-OC single-atom electrocatalyst described in the present invention is: 1 mg of the prepared core-shell structure Zn-OC single-atom electrocatalyst is dispersed in a mixed solution of water, ethanol and Nafion, and after ultrasonic dispersion, the solution is dripped onto a disk-ring disk electrode, dried in air, and tested using a three-electrode system, in which a Hg / HgO electrode and a platinum sheet are used as a reference electrode and a counter electrode, respectively, and the electrolyte is an O2-saturated 0.1M KOH solution. The selectivity of the core-shell structure Zn-OC single-atom electrocatalyst for catalytic synthesis of H2O2 is as high as 90%.

[0020] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0021] 1. Compared with the traditional anthraquinone method, the method for preparing H2O2 based on the core-shell structure of Zn-OC single-atom electrocatalyst of the present invention is green and environmentally friendly and can be directly used in fields such as sewage treatment.

[0022] 2. The tannic acid in the present invention not only provides a sufficient oxygen coordination environment for the atomically dispersed zinc, but also forms a core-shell structure that is beneficial to the transmission of oxygen and intermediates.

[0023] 3. The core-shell structure Zn-OC single-atom electrocatalyst provided by the present invention is evaluated by the following method: the catalytic performance of the catalyst is tested using a rotating ring disk electrode and an electrochemical workstation. The catalyst is ultrasonically dispersed in a mixed solution of water, ethanol and Nafion. After uniform dispersion, an appropriate amount is added dropwise to the rotating disk ring disk electrode and dried naturally. The electrolyte is a 0.1M KOH solution. Linear sweep voltammetry (LSV) and cyclic voltammetry (CV) tests are carried out in an oxygen-saturated electrolyte. The results show that the core-shell structure Zn-OC single-atom electrocatalyst has a selectivity of up to 90% for catalytic synthesis of H2O2. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a SEM image of the Zn-OC single atom electrocatalyst prepared in Example 1.

[0025] Figure 2 is the XRD pattern of the Zn-OC single atom electrocatalyst prepared in Example 1.

[0026] Figure 3 This is the HADDF-STEM image of the Zn-OC single-atom electrocatalyst prepared in Example 1.

[0027] Figure 4 This is the H2O2 selectivity curve of the Zn-OC single atom electrocatalyst prepared in Example 1.

[0028] Figure 5 is the number of electrons transferred by the Zn-OC single atom electrocatalyst prepared in Example 1 in the oxygen reduction reaction. DETAILED DESCRIPTION

[0029] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention. Example 1

[0030] Step S1: Pour 120 mL of methanol solution containing 2.38 g of zinc nitrate into 120 mL of methanol solution containing 2.13 g of 2-methylimidazole, let stand for 12 h, then perform solid-liquid separation, and dry to obtain polyhedral ZIF-8;

[0031] Step S2: 0.4 g of the polyhedral ZIF-8 obtained in step S1 was stirred in 200 mL, 5 g / L tannic acid solution for 10 min, and then solid-liquid separation and drying were performed to obtain ZIF-8 with a hollow structure;

[0032] Step S3: 0.2 g of the hollow structure ZIF-8 obtained in step S2 is placed in a tube furnace, and 0.04 g of sublimated sulfur is placed in front of the material, and the temperature is increased to 600° C. at a heating rate of 3° C. / min under a nitrogen atmosphere for 3 h, and then naturally cooled to room temperature;

[0033] Step S4: Soak the material obtained in step S3 in 2M hydrochloric acid at room temperature for 24 hours, then filter it, wash it with water until it is neutral, and then dry it at 80° C. to obtain a core-shell structured Zn-OC single-atom electrocatalyst.

[0034] 1 mg of the core-shell structured Zn-OC single-atom electrocatalyst prepared above was dispersed in a mixed solution of water, ethanol and Nafion. After ultrasonic dispersion, an appropriate amount of the solution was added dropwise to the glassy carbon of the disk-ring disk electrode and dried in the air. The three-electrode system was used for testing, with the Hg / HgO electrode and platinum sheet as the reference electrode and counter electrode, respectively, and the electrolyte was an O2-saturated 0.1M KOH solution. During the test, the scanning speed was 10mV / s, and the scanning range was 0V~1.2V (vs. RHE). The core-shell structured Zn-OC single-atom electrocatalyst had a selectivity of up to 90% for catalytic synthesis of H2O2. Example 2

[0035] Step S1: Pour 600 mL of methanol solution containing 11.90 g of zinc nitrate into 600 mL of methanol solution containing 10.65 g of 2-methylimidazole, let stand for 12 h, perform solid-liquid separation and drying to obtain polyhedral ZIF-8;

[0036] Step S2: 2 g of the polyhedral ZIF-8 obtained in step S1 is placed in 1000 mL of a 5 g / L tannic acid solution, followed by solid-liquid separation and drying to obtain a hollow structured ZIF-8;

[0037] Step S3: placing 1 g of the hollow structured ZIF-8 obtained in step S2 in a tube furnace, and placing 0.2 g of sublimated sulfur in front of the material, heating the mixture to 600° C. at a heating rate of 3° C. / min under a nitrogen atmosphere for 3 h, and then naturally cooling the mixture to room temperature;

[0038] Step S4: Soak the material obtained in step S3 in 2M hydrochloric acid at room temperature for 24 hours, then filter it, wash it with water until it is neutral, and then dry it at 80° C. to obtain a core-shell structured Zn-OC single-atom electrocatalyst. Example 3

[0039] Step S1: Pour 120 mL of methanol solution containing 2.38 g of zinc nitrate into 120 mL of methanol solution containing 2.13 g of 2-methylimidazole, let stand for 12 h to obtain solid-liquid separation, and dry to obtain polyhedral ZIF-8;

[0040] Step S2: 0.4 g of the polyhedral ZIF-8 obtained in step S1 is placed in 200 mL of a 5 g / L tannic acid solution, followed by solid-liquid separation and drying to obtain a hollow structured ZIF-8;

[0041] Step S3: 0.2 g of the hollow structure ZIF-8 obtained in step S2 is placed in a tube furnace, and 0.04 g of sublimated sulfur is placed in front of the material, and the temperature is increased to 600° C. at a heating rate of 5° C. / min under a nitrogen atmosphere for 4 hours, and then naturally cooled to room temperature;

[0042] Step S4: Soak the material obtained in step S3 in 2M hydrochloric acid at room temperature for 24 hours, then filter it, wash it with water until it is neutral, and then dry it at 60° C. to obtain a core-shell structured Zn-OC single-atom electrocatalyst. Example 4

[0043] Step S1: Pour 120 mL of methanol solution containing 2.38 g of zinc nitrate into 120 mL of methanol solution containing 2.13 g of 2-methylimidazole, let stand for 12 h to obtain solid-liquid separation, and dry to obtain polyhedral ZIF-8;

[0044] Step S2: 0.4 g of the polyhedral ZIF-8 obtained in step S1 was placed in 200 mL of 8 g / L tannic acid solution, stirred for 8 min, and then subjected to solid-liquid separation and drying to obtain ZIF-8 with a hollow structure;

[0045] Step S3: 0.2 g of the hollow structure ZIF-8 obtained in step S2 is placed in a tube furnace, and 0.04 g of sublimated sulfur is placed in front of the material, and the temperature is increased to 600° C. at a heating rate of 3° C. / min under a nitrogen atmosphere for 3 h, and then naturally cooled to room temperature;

[0046] Step S4: Soak the material obtained in step S3 in 2M sulfuric acid at room temperature for 24 hours, then filter it, wash it with water until it is neutral, and then dry it at 80° C. to obtain a core-shell structured Zn-OC single-atom electrocatalyst.

[0047] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a core-shell structure Zn-OC single-atom electrocatalyst for synthesizing H2O2, characterized in that The specific steps are: Step S1: mixing a methanol solution of 2-methylimidazole and a methanol solution of zinc salt, and allowing to stand, and then performing solid-liquid separation and drying to obtain polyhedral ZIF-8; Step S2: The polyhedral ZIF-8 obtained in step S1 is stirred in a tannic acid solution, and then solid-liquid separation and drying are performed to obtain ZIF-8 with a hollow structure; Step S3: placing the hollow structure ZIF-8 obtained in step S2 in a tube furnace, placing sublimated sulfur in front of the ZIF-8, heating to 600°C at a heating rate of 1-10°C / min under an inert gas atmosphere, and keeping the temperature constant for 2-4h, and then naturally cooling to room temperature; Step S4: soaking the material obtained in step S3 with an acid solution, then filtering, washing with water until neutral, and drying to obtain a core-shell structured Zn-OC single-atom electrocatalyst for synthesizing H2O2, wherein the metal Zn in the core-shell structured Zn-OC single-atom electrocatalyst is supported on the nitrogen / sulfur co-doped carbon material in the form of a single atom, and the loading amount of the metal Zn is 2wt%~8wt%.

2. The method for preparing a core-shell structured Zn-OC single-atom electrocatalyst for synthesizing H2O2 according to claim 1, characterized in that: The molar ratio of 2-methylimidazole to zinc salt in step S1 is 1-8:

1.

3. The method for preparing a core-shell structured Zn-OC single-atom electrocatalyst for synthesizing H2O2 according to claim 1, characterized in that: The concentration of tannic acid in step S2 is 3-8 g / L, and the stirring treatment time is 10-20 min.

4. The method for preparing a core-shell structured Zn-OC single-atom electrocatalyst for synthesizing H2O2 according to claim 1, characterized in that: The mass ratio of the hollow structure ZIF-8 to the sublimated sulfur in step S3 is 1:4-8.

5. The method for preparing a core-shell structured Zn-OC single-atom electrocatalyst for synthesizing H2O2 according to claim 1, characterized in that: The inert gas in step S3 is one or more of nitrogen, argon or helium.

6. The method for preparing a core-shell structured Zn-OC single-atom electrocatalyst for synthesizing H2O2 according to claim 1, characterized in that: The acid solution in step S4 is one or more of hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid or acetic acid, the concentration of the acid solution is 0.5-4M, the acid solution treatment temperature is 25-100°C, and the acid solution treatment time is 2-24h.

7. The method for preparing a core-shell structured Zn-OC single-atom electrocatalyst for synthesizing H2O2 according to claim 1, characterized in that The specific steps are: Step S1: Pour 120 mL of methanol solution containing 2.38 g of zinc nitrate into 120 mL of methanol solution containing 2.13 g of 2-methylimidazole, let stand for 12 h, perform solid-liquid separation and drying to obtain polyhedral ZIF-8; Step S2: 0.4 g of the polyhedral ZIF-8 obtained in step S1 is dispersed in 200 mL of a 5 g / L tannic acid solution and stirred for 10 min, followed by solid-liquid separation and drying to obtain ZIF-8 with a hollow structure; Step S3: 0.2 g of the hollow structure ZIF-8 obtained in step S2 is placed in a tube furnace, and 0.04 g of sublimated sulfur is placed in front of the ZIF-8, and the temperature is increased to 600° C. at a heating rate of 3° C. / min under a nitrogen atmosphere for 3 h, and then naturally cooled to room temperature; Step S4: Soak the material obtained in step S3 in 2M hydrochloric acid at room temperature for 24 hours, then filter it, wash it with water until it is neutral, and then dry it at 80°C to obtain a core-shell structured Zn-OC single-atom electrocatalyst for synthesizing H2O2.

8. The method for preparing a core-shell structured Zn-OC single-atom electrocatalyst for synthesizing H2O2 according to claim 1, characterized in that The specific process of synthesizing H2O2 is as follows: 1 mg of the prepared core-shell structure Zn-OC single atom electrocatalyst is dispersed in a mixed solution of water, ethanol and Nafion. After ultrasonic dispersion, the solution is dripped onto the disk-ring disk electrode and dried in the air. The three-electrode system is used for testing, with the Hg / HgO electrode and platinum sheet as the reference electrode and counter electrode respectively. The electrolyte is an O2-saturated 0.1M KOH solution. The selectivity of the core-shell structure Zn-OC single atom electrocatalyst for catalytic synthesis of H2O2 is as high as 90%.